The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.14257/ijca.2014.7.7.35
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Generation Mechanism and Influencing Factors of Metal Machining Fluid Oil Mist Microparticles

Abstract: Based on the dangers of suspended oil mist microparticles from machining to the environment and health of worker. A theoretical analysis on the generation mechanism of cutting fluid oil mist and an experimental study on its influencing factors were carried out in this paper. The experiment was conducted in closed lathe with flood cutting fluid feed system. A droplet diameter measuring system was equipped in the dense region of oil mist, which enables to observe the droplet distribution in air and scan the morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Cost encountered in flood machining conditions (inventory, maintenance, preparation, disposal of chips and fluids) is much more than MQL costing. Literature found that almost 15-20 % of the overall machining cost is incurred for coolants and lubricants in industries [9][10][11][12]. According to DeVries et al, [13] among total operation costs, 8-16% of costing is related to metalworking fluids, and MQL significantly reduces these costs as in MQL, there is no cost for drying the chips and cleaning the workpiece and chips.…”
Section: Introductionmentioning
confidence: 99%
“…Cost encountered in flood machining conditions (inventory, maintenance, preparation, disposal of chips and fluids) is much more than MQL costing. Literature found that almost 15-20 % of the overall machining cost is incurred for coolants and lubricants in industries [9][10][11][12]. According to DeVries et al, [13] among total operation costs, 8-16% of costing is related to metalworking fluids, and MQL significantly reduces these costs as in MQL, there is no cost for drying the chips and cleaning the workpiece and chips.…”
Section: Introductionmentioning
confidence: 99%
“…Besides environmental and health issues, the costs associated with the applications, storage and disposal of cutting fluids are also a concern. About 15-20 % of the overall machining costs are related to cooling and lubricating fluids [29][30][31][32]. Most of the research studies involving machining with MQL, as a cutting medium, have been mainly concerned with the turning, drilling and grinding process.…”
Section: Introductionmentioning
confidence: 99%
“…MQL is a sustainable manufacturing technique that is safe for the environment and the worker and is cost effective [2][3][4][5]. The cost of cutting fluids range from 7 to 17% of the total machining cost while another estimate gives this cost as 15-20 % of total machining cost compared to the tool cost which ranges from 2 to 4% [6][7][8][9][10][11]. Therefore minimization of metal working fluids can serve as a direct indicator of sustainable manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Besides environmental and health issues, costs associated with the applications, storage and disposal of cutting fluids are also a concern. About 15 % -20 % of the overall machining costs are related to cooling and lubricating fluids [5,8,32]. The annual global consumption of cutting fluids by the year 2007 was 640 million gallons [4].…”
Section: Introductionmentioning
confidence: 99%